Cancer Pain and Depression: A Systematic Review of Age-Related Patterns - Lucia Gagliese; Lynn R Gauthier; Gary Rodin (Pain Research and Management, 2007)
BACKGROUND: Pain is a common and debilitating symptom experienced by cancer patients of all ages. Cancer pain is associated with elevated levels of depression; however, age-related patterns in this relationship remain unclear. This information is important to provide effective palliation of pain and depression to the growing numbers of older cancer patients.